Small-Molecule Compound SYG-180-2-2 to Effectively Prevent the Biofilm Formation of Methicillin-Resistant Staphylococcus aureus - Rao, Lulin; Sheng, Yaoguang; Zhang, Jiao; Xu, Yanlei; Yu, Jingyi; Wang, Bingjie; Zhao, Huilin; Wang, Xinyi; Guo, Yinjuan; Wu, Xiaocui; Song, Zengqiang; Yu, Fangyou; et al. (Frontiers in Microbiology, 2022)
The resistance of methicillin-resistant Staphylococcus aureus (MRSA) has augmented due to the abuse of antibiotics bringing about the treatment of infection hardly especially with the formation of biofilm. Thus, it is essential to develop antimicrobials. Here we synthesized a novel small-molecule compound, which we termed SYG-180-2-2 (C21H16N2OSe), that had antibiofilm activity. The aim of this study was to demonstrate the antibiofilm effect of SYG-180-2-2 against clinical MRSA isolates at subinhibitory concentration (4 μg/ml). In this study, it was showed significant suppression in biofilm formation when treated with SYG-180-2-2, the inhibition ranged between 65.0% and 85.2%. Subsequently, confocal laser scanning microscopy and bacterial biofilm metabolism activity assay further demonstrated that the SYG-180-2-2 could suppress biofilm. Additionally, SYG-180-2-2 reduced the bacterial adhesion and polysaccharide intercellular adhesin (PIA) production. It was found that the expression of icaA and other biofilm-related genes were downregulated as evaluated by RT-qPCR. At the same time, icaR and codY were upregulated when biofilms were treated with SYG-180-2-2. Based on the above results, we speculate that SYG-180-2-2 inhibits the formation of biofilm by affecting cell adhesion and the expression of genes related to PIA production. Above all, SYG-180-2-2 had no toxic effects on human normal alveolar epithelial cells BEAS-2B. Collectively, the small-molecule compound SYG-180-2-2 is a safe and effective antibacterial agent for inhibiting MRSA biofilm.